Self-contracting oxidized starch/gelatin hydrogel for noninvasive wound closure and wound healing - Qin Mao; Oskar Hoffmann; Kun Yu; Fei Lu; Guangqian Lan; Fangyin Dai; Songmin Shang; Ruiqi Xie (Materials & Design, 2020)
Major challenges in traditional wound closure methods (e.g. using sutures and skin staplers) remain inadequately unaddressed; these invasive treatments induce extra puncture wounds, anesthetic side effects, and severe scarring. Herein, an oxidized starch/gelatin-based shape memory hydrogel (OSG) was fabricated as a self-contracting wound dressing to facilitate noninvasive wound closure. The self-contracting properties were attributed by introducing crosslink net-points in the hydrogel polymer structure through Schiff base reaction between oxidized starch (OS) and gelatin. We systematically investigated the self-contracting properties to determine the feasibility of the hydrogel to treat wounds and promote wound closure noninvasively. Following elongation, OSGs could be entirely fixed in a temporary shape at 4 °C, and then contracted under infrared irradiation (IR) for shape memory activation near human physiological temperature (38 °C), providing sufficient recovery force (4 kPa) for successful noninvasive wound closure. Additionally, H&E staining revealed that thicker epidermis and dermis layers were achieved upon OSG treatment, confirming that the OSG facilitated tissue reconstruction in an in vivo rabbit model. Moreover, the OSG-treated wounds displayed smoother skin and no visible scarring compared to sutured wounds. Such excellent performance suggests that OSG hydrogel exhibits high potential as an alternative to medical sutures to facilitate noninvasive would closure.